PEMBUATAN MAGNETIK BARIUM M-HEKSAFERIT YANG DIDOPING ION Cu - seri dermayu siregar (Saintia Fisika, 2013)
Permanent magnet of Barium M-Heksaferit doped by Cu ions were synthetized with formula BaFe12-x Cux O19, where (x = 0.1, 0.2, 0.3, 0.4, 0.5, and 0.6 % mol). Preparation process of raw materials ranging from mixing and milling Barium Carbonate (BaCO3), Hematite (Fe2O3) and copper oxide (CuO) by wet milling in distilled water medium have done during 20 hours. Material was then dried at a temperature of 1000C for 24 h, calcined at a temperature of 10000C by using electric furnace for 2 hours. The crystallinite size was determined to be 400 mesh (38 µm). Sintering process was carried out by using electric furnace Thermolyn at temperature 11000C. Characterization include SEM / EDX, physical properties (density and porosity by Archimedes method), using permagraph magnetic properties and crystal structure by XRD. Elemental analysis on testing SEM / EDX showed that Fe element has the greatest wt% (52.61%). The sample detected element Al as an impurity. The hysteresis curve can be seen the value of magnetic BaFe12-x Cux O19 who have made ​​bulk density produces approximately 3.8 to 5.2 g/cm3, porosity of 1.6 to 10.7%, a strong magnet from 43.36 to 100.42 G , remanent magnetic induction (Br) 20-320 G, koercivitas (HcJ) 1, 07 to 9.22 kOe and enenrgy production (BH) max from 0.05 to 0.92 kGOe. Effect of Cu doping tends to increase the value of density, lower porosity, and improve the magnetic properties.